If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -29 + X = -3 Solving -29 + X = -3 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '29' to each side of the equation. -29 + 29 + X = -3 + 29 Combine like terms: -29 + 29 = 0 0 + X = -3 + 29 X = -3 + 29 Combine like terms: -3 + 29 = 26 X = 26 Simplifying X = 26
| 15=-9+4w+2w | | 7y=42y+60 | | 21x=176 | | 42-4t=3t | | 3xy-2x=4p-1 | | X^2+8x=2x+40 | | 15=-9+4w+3w | | 3x+11x-20=0 | | 2x+10=5x+25 | | 84=3w | | 17-(3+b)=b | | 8a+15+a^2=0 | | 12x+16=4x+56 | | 5000x^2+60x=0 | | x+3-4x=6x+10 | | X-5=7-x | | 500x^2+6x=0 | | 1+(-3)= | | 3y-2(y-1)=6-(4+1) | | 0=k^2+12k+32 | | -7+4x=6x-5x | | 3x+18=99 | | 11x-y=-15 | | -66=2b-6(6+2b) | | 3x^2-6x-12y+3y^2-12=0 | | 6x+16=-5 | | 2u=38 | | -6x-1+3x=-7x-7 | | 8(y+6)+27=99 | | 16a-8a-8b= | | y=x+(x*1.2) | | 3x^2-6x-12y+3y^2+12=0 |